Brothers in the Great War Siblings, masculinity and emotions - Maynard, Linda (Manchester University Press, 2021)
Drawing on a broad range of personal accounts, this is the first detailed study of siblinghood in wartime. The relative youth of the fighting men of the Great War intensified the emotional salience of sibling relationships. Long separations, trauma and bereavement tested sibling ties forged through shared childhoods, family practices, commitments and interests. We must not equate the absence of a verbal language of love with an absence of profound feelings. Quieter familial values of kindness, tolerance and unity, instilled by parents and reinforced by moral instruction, strengthened bonds between brothers and sisters. Examining the nexus of cultural and familial emotional norms, this study reveals the complex acts of mediation undertaken by siblings striving to reconcile conflicting obligations to society, the army and loved ones in families at home. Brothers enlisted and served together. Siblings witnessed departures and homecomings, shared family responsibilities, confided their anxieties and provided mutual support from a distance via letters and parcels. The strength soldier-brothers drew from each other came at an emotional cost to themselves and their comrades. The seismic casualties of the First World War proved a watershed moment in the culture of mourning and bereavement. Grief narratives reveal distinct patterns of mourning following the death of a loved sibling, suggesting a greater complexity to male grief than is often acknowledged. Surviving siblings acted as memory keepers, circumventing the anonymisation of the dead in public commemorations by restoring the particular war stories of their brothers.